Child Friendly App for Spelling Training - Santos, Ana Sucena; Carneiro, João Falcão; Silva, Ana Filipa; Abreu, Paulo; Garrido, Cristina; Marques, Cátia; Santos, Raquel; Restrivo, Teresa (International Journal of Online and Biomedical Engineering (iJOE), 2020)
Spelling skills are usually more difficult to acquire than reading skills. Nonetheless research based intervention proposals are scarce for spelling skills. In this study the impact of a child friendly spelling app on spelling skills is assessed. Results indicate an increase on spelling skills after training with the app.